The Effect of Integrated Marketing Communications and Service Quality on Purchase Decisions Mediated by Consumer Satisfaction in the Covid-19 Pandemic Era (Study at Maybank Finance Java Non Jabodetabek Area) - Jimmy Yosal; P.M. Budi Haryono; Soegeng Wahyoedi (Budapest International Research and Critics University, 2021)
This research is an explanatory research by applying the survey method, in which proposed to examine the effect of integrated marketing communication and service quality on purchase decisions mediated by consumer satisfaction at Maybank Finance, Java Area, Non Jabodetabek in the Covid-19 Pandemic Era. The sample of this research is 100 consumers who are new debtors who will do financing at Maybank Finance in the Java Region of the Non-jabodetabek area. Data obtained through questionnaires, that was spreaded to respondents who were selected by purposive sampling method. The analytical technique used in this study is the Structural Equation Model (SEM) using the SMARTPls 3 program. The results reveal that the direct influence of integrated marketing communication and service quality on consumer purchase decisions is no significant. The direct effect of consumer satisfaction on consumer purchase decisions is positive and significant, in which the path coefficient of 0.536 with a p value of 0.000. The results of the mediation effect test show that consumer satisfaction does not play a role in mediating the effect of integrated marketing communications on consumer purchase decisions. Consumer satisfaction plays a role in mediating the effect of service quality on purchase decisions.